A conserved role for CUP‐SHAPED COTYLEDON genes during ovule development. (23rd July 2015) - Gonçalves, Beatriz; Hasson, Alice; Belcram, Katia; Cortizo, Millán; Morin, Halima; Nikovics, Krisztina; Vialette‐Guiraud, Aurélie; Takeda, Seiji; Aida, Mitsuhiro; Laufs, Patrick; Arnaud, Nicolas
Summary The evolution of plant reproductive strategies has led to a remarkable diversity of structures, especially within the flower, a structure characteristic of the angiosperms. In flowering plants, sexual reproduction depends notably on the development of the gynoecium that produces and protects the ovules. In Arabidopsis thaliana, ovule initiation is promoted by the concerted action of auxin with CUC1 (CUP‐SHAPED COTYLEDON1) and CUC2, two genes that encode transcription factors of the NAC family (NAM/ATAF1, 2/CUC). Here we highlight an additional role for CUC2 and CUC3 in Arabidopsis thaliana ovule separation. While CUC1 and CUC2 are broadly expressed in the medial tissue of the gynoecium, CUC2 and CUC3 are expressed in the placental tissue between developing ovules. Consistent with the partial overlap between CUC1, CUC2 and CUC3 expression patterns, we show that CUC proteins can physically interact, both in yeast cells and in planta. We found that the cuc2;cuc3 double mutant specifically harbours defects in ovule separation, producing fused seeds that share the seed coat, and suggesting that CUC2 and CUC3 promote ovule separation in a partially redundant manner. Functional analyses show that CUC transcription factors are also involved in ovule development in Cardamine hirsuta. Additionally we show a conserved expression pattern of CUC orthologues between ovule primordia in other phylogenetically distant species with different gynoecium architectures. Taken together these results suggest an ancient role for CUC transcription factors in ovule separation, and shed light on the conservation of mechanisms involved in the development of innovative structures.